Transfer of a single fresh in vitro‐produced embryo may prevent twin pregnancy without compromising the fertility of the cow. Issue 4 (7th January 2022) - López‐Gatius, Fernando; Saleri, Roberta; De Rensis, Fabio; Llobera‐Balcells, Monica; Garcia‐Ispierto, Irina
Contents: This study examines whether the transfer of a fresh in vitro‐produced (IVP) embryo can avoid the risk of twin pregnancy without reducing the fertility of a cow. The study population was comprised of 416 lactating dairy cows synchronized for oestrus: 294 were fixed‐time inseminated (AI cows), and 122 were given GnRH treatment at the time of embryo transfer (ET) an IVP embryo (ET cows). Of the 416 cows, 167 (40.1%) became pregnant. Twin pregnancy was recorded in 20.8% of the AI pregnant cows (21/101), whereas no ET cows had twins (0/66). Significant interaction ( p  < .01) was observed between breeding technique and the period of the year for the likelihood of pregnancy. This meant that using AI cows during the warm period (May–September) as reference, the odds ratio for pregnancy in ET cows during the warm period was 3.4 ( p  = .001). In conclusion, transfer of a single fresh IVP embryo proved useful to prevent the risk of twin pregnancy without affecting fertility.